Student’s Attitudes Towards Probability and Statistics and Academic Achievement on Higher Education - de Oliveira Júnior, Ailton Paulo; Zamora, Pedro Rosental; Azevedo de Oliveira, Lucas; Costa de Souza, Thiago (Acta Didactica Napocensia, 2018)
A simple analysis of the learners' academic status at different levels of education shows that these learners have poor performance in probability and statistics subject and they have negative attitude to this subject. Therefore, the aim of this study is to investigate the relationship between the attitude and academic achievement of 134 students of three classes of a compulsory subject of the fourth period aimed at probabilistic and statistical content, at a federal university, in the state of Säo Paulo, Brazil, at the end of 2017. We used the Auzmendi Scale (1992) that considers attitudes towards mathematics and statistics, at the same time, being composed of five basic factors (utility, anxiety, trust, pleasure and motivation). Some of the results indicate that there is an indication that students lack confidence in solving statistical and probabilistic problems, noting that there is no great anxiety about Probability and Statistics, however, they do not feel confident about solving problems probabilistic and statistical. And they present initial motivation and this fact generates better results in the first evaluation of the discipline that deals with basic concepts of Combinatorial Analysis and Probability.